Pelaksanaan Program Layanan Konseling Dengan Pendekatan Lintas Budaya Dan Seni - Ahmad Fauzan Yusman; Neviyarni Suhaili; Mudjiran Mudjiran; Herman Nirwana (FBS Universitas Negeri Padang, 2021)
This article aims to see how the implementation of counseling services with a cross-cultural approach and counseling outreach services in non-performing arts competitions. Written by a qualitative method with a descriptive approach, data obtained from observation, documentation and interviews. Research that focuses on the implementation of counseling services at SMA Negeri 2 Padang Panjang by paying attention to the Counseling Guidance service and the extracurricular development of the Youth Counseling Information Center (PIK-R). It is found that in the socialization of counseling can be carried out by counselors and counselees with different cultural backgrounds. Students who come from certain ethnicities and religions can still get optimal service. Besides that, PIK-R's extracurricular role in realizing counseling socialization in the form of performances and art competitions, is creative and effective in achieving the objectives of counseling in general. Counseling guidance which partly has a negative stigma for students will think otherwise, if this kind of socialization is carried out continuously.